Beyond the Fear of Deportation: Understanding Unauthorized Immigrants' Ambivalence Toward the Police. (August 2019) - Armenta, Amada; Rosales, Rocío
This article draws on in-depth interviews and ethnography to examine unauthorized Mexican immigrants' perceptions of and experiences with police in Los Angeles and Philadelphia. Most existing research focuses on immigrants' fears of deportation as the primary determinant of negative attitudes toward the police. We add to this body of work by arguing that police interactions serve as important moments of legal socialization that also contribute to undocumented immigrants' legal attitudes. Our findings reveal that undocumented immigrants express a great deal of ambivalence about American police, believing them to be both trustworthy and overly punitive. Ultimately, the ambivalence that undocumented immigrants feel about the police mirrors the tension between inclusion and exclusion that characterizes immigrant life in the United States.